Methodological Investigations in Agent-Based Modelling With Applications for the Social Sciences - Silverman, Eric (Methodos Series, Methodological Prospects in the Social Sciences, 2018)
This open access book examines the methodological complications of using complexity science concepts within the social science domain.  The opening chapters take the reader on a tour through the development of simulation methodologies in the fields of artificial life and population biology, then demonstrates the growing popularity and relevance of these methods in the social sciences.  Following an in-depth analysis of the potential impact of these methods on social science and social theory, the text provides substantive examples of the application of agent-based models in the field of demography.  This work offers a unique combination of applied simulation work and substantive, in-depth philosophical analysis, and as such has potential appeal for specialist social scientists, complex systems scientists, and philosophers of science interested in the methodology of simulation and the practice of interdisciplinary computing research.